Improving the reference standard for the diagnosis of canine visceral leishmaniasis : a challenge for current and future tests - Teixeira, Ana Izabel Passarella (2019)
BACKGROUND Studies aimed at validating canine visceral leishmaniasis diagnostic tests present heterogeneous results regarding test accuracy, partly due to divergences in reference standards used and different infection evolution periods in animals. OBJECTIVE This study aimed to evaluate the accuracy of the rapid test-dual path platform (TR-DPP) (Biomanguinhos®), EIE-Leishmaniose-Visceral-Canina-Biomanguinhos (EIE-LVC) (Biomanguinhos®), enzyme-linked immunosorbent assay (ELISA) rK39 (in-house), and the direct agglutination test (DAT-Canis) against a reference standard comprising parasitological and molecular techniques. METHODS A phase II/III validation study was carried out in sample sera from 123 predominantly asymptomatic dogs living in an area endemic for visceral leishmaniasis. FINDINGS Sixty-nine (56.1%) animals were considered infected according to the reference standard. For each test, the sensitivity and specificity, respectively, were as follows: TR-DPP, 21.74% [confidence interval (CI)95% 13.64% to 32.82%] and 92.59% (CI95% 82.45% to 97.08%); EIE-LVC, 11.59% (CI95% 5.9% to 21.25%) and 90.74% (CI95% 80.09% to 95.98%); ELISA rK39, 37.68% (CI95% 27.18% to 49.48%) and 83.33% (CI95% 71.26% to 90.98%); and DAT-Canis, 18.84% (CI95% 11.35% to 29.61%) and 96.30% (CI95% 87.46% to 98.98%). CONCLUSION We concluded that improving the sensitivity of serum testing for diagnosing asymptomatic dogs must constitute a priority in the process of developing new diagnostic tests to be used in the visceral leishmaniasis control program in Brazil.